2015
DOI: 10.1021/acs.energyfuels.5b01668
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Acidogenic Fermentation of Corn Stover Hydrolysates by Thermal Pretreatment with Diluted Formic Acid as Catalyst

Abstract: In this study, formic acid was selected as the catalyst to pretreat corn stover which is also a good substrate for biohydrogen and biogas production. The pretreatment effect and the acidogenic characteristic of hydrolysates were also evaluated. Using corn stover (8.00 g) mixed with 72.00 g of formic acid (2.5%) at temperature 190 °C for reaction time 10 min, 17.36 ± 0.80 g/L glucose, 18.13 ± 0.83 g/L xylose, 5.45 ± 0.25 g/L arabinose, 3.88 ± 0.17 g/L acetic acid, and 1.96 ± 0.07 g/L furfural were obtained in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Jin Xu et al . used dilute formic acid to treat the corn stover and found that the hydrolysate could be used as a good substrate for the acid‐producing fermentation process. Zhao Xu et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jin Xu et al . used dilute formic acid to treat the corn stover and found that the hydrolysate could be used as a good substrate for the acid‐producing fermentation process. Zhao Xu et al .…”
Section: Resultsmentioning
confidence: 99%
“…Zhao Xu et al [17] studied the optimal conditions for the pretreatment of corn stover with dilute acetic acid and proposed a two-phase biogas fermentation system suitable for the fermentation of corn stover. Comparing to the amount of furfural between 0.6 and 2.21 g/L, we obtained 17.22-29.89 g/L of total sugar under different experimental temperature in the beginning 5 min, which was easier to be utilized by bacteria to produce Volatile Fatty Acid (VFA) [11,16]. At the same time, accounting around 80% proportion in the hydrolysate pretreated bynitric acid, acetic acid, and butyric acid have the characteristics of butyric acid fermentation type, which have been proved beneficial to the subsequent biogas production under the similar reaction conditions to Zhang et al [11].…”
Section: Effect Of Prehydrolysate On the Biogas Fermentationmentioning
confidence: 94%
See 1 more Smart Citation
“…Temperature and reaction time are the most important factor that plays a major role in this pretreatment process [13]. This method proved to display a significant effect on the disruption of biomass and biofiber such as pelletized corn stover, rice hulls, kenaf, Tahoe mix, and switch grass [14][15][16]. Although this method was reported to display a positive effect on enzymatic saccharification process, this method is not selective and less effective for the biomass with less lignin content.…”
Section: Pretreatment Of Biomass and Biofiber For Liquid Biofuelmentioning
confidence: 99%
“…During the bio-refinery process of corncob, pretreatment is an essential step to break down the biomass structure and allow bio-degradation of the polysaccharide in biomass [5,6]. Among all studied pretreatment methods, dilute acid pretreatment is probably the most commonly applied method [7][8][9]. Dilute sulfuric acid has been widely used in dilute acid pretreatment for its availability and high removal capacity for hemicellulose [10].…”
Section: Introductionmentioning
confidence: 99%